2015
DOI: 10.14295/bds.2015.v18i2.1077
|View full text |Cite
|
Sign up to set email alerts
|

What is the best protocol for bonding resin-modified glass ionomer cement to composite resin?

Abstract: Objective: The objective of this study was to evaluate the bond strength of resin-modified glass ionomer cement (RMGIC) to composite resin considering the use of conventional and self-etching adhesive systems. Material and Methods: 60 RMGIC blocks (Riva, SDI) measuring 4 x 4 x 4 mm. were constructed. On the blocks, the application of different protocols of adhesive systems (n = 10) was carried out: Group 1 (Control) - without application of adhesive agent; Group 2 - 37% phosphoric acid + conventional adhesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Reports indicate that applying bonding agents enhances the bond strength between RMGI and composite [28,[44][45][46][47][48]. The bond strength of RMGI to composite resin may differ based on the specific adhesive system employed [28,44,45,47].…”
Section: Layering Over Resin-modified Glass Ionomersmentioning
confidence: 99%
“…Reports indicate that applying bonding agents enhances the bond strength between RMGI and composite [28,[44][45][46][47][48]. The bond strength of RMGI to composite resin may differ based on the specific adhesive system employed [28,44,45,47].…”
Section: Layering Over Resin-modified Glass Ionomersmentioning
confidence: 99%
“…Their study recommended the application of self-etch over etch and rinse adhesives. Barcellos et al 76 reported that acid etching before applying an etch and rinse (Adper Single Bond 2) or self-etching adhesive (Clearfil SE Bond) increased the bond strength of RMGI to the composite resin.…”
Section: Dovepressmentioning
confidence: 99%